Research priorities for freshwater mussel conservation assessment. (March 2019) - Ferreira-Rodríguez, Noé; Akiyama, Yoshihiro B.; Aksenova, Olga V.; Araujo, Rafael; Christopher Barnhart, M.; Bespalaya, Yulia V.; Bogan, Arthur E.; Bolotov, Ivan N.; Budha, Prem B.; Clavijo, Cristhian; Clearwater, Susan J.; Darrigran, Gustavo; et al.
Abstract: Freshwater mussels are declining globally, and effective conservation requires prioritizing research and actions to identify and mitigate threats impacting mussel species. Conservation priorities vary widely, ranging from preventing imminent extinction to maintaining abundant populations. Here, we develop a portfolio of priority research topics for freshwater mussel conservation assessment. To address these topics, we group research priorities into two categories: intrinsic or extrinsic factors. Intrinsic factors are indicators of organismal or population status, while extrinsic factors encompass environmental variables and threats. An understanding of intrinsic factors is useful in monitoring, and of extrinsic factors are important to understand ongoing and potential impacts on conservation status. This dual approach can guide conservation status assessments prior to the establishment of priority species and implementation of conservation management actions. Highlights: We develop a portfolio of priority research topics for freshwater mussel conservation assessment. The portfolio summarizes the knowledge of a multidisciplinary, global team of scientists working in this area. Research priorities are divided into two categories, intrinsic and extrinsic factors. We discuss how practitioners can leverage this information to improve conservation actions.